Pelaksanaan Pemberian Pembebasan Bersyarat (Pb) pada Warga Binaan di Rumah Tahanan Negara Kelas II b Gianyar pada Masa Pandemi Covid 19 - I Made Irvan Ariansyah Putra; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Jurnal Preferensi Hukum, 2021)
Indonesia is a country of law, therefore the imposition of sanctions in the form of detention is a way to provide a deterrent effect on the actions committed, namely by providing guidance, granting the right to parole is a form of guidance aimed at enabling prisoners to interact healthily with the community. The purpose of this research is to analyze the legal arrangements regarding the system of guiding prisoners through efforts to grant parole rights at the Gianyar Class II B State Prison and the obstacles in the implementation of the provision of parole in the Gianyar Class II B State Prison during the Covid-19Pandemic. The method used is empirical with legal data sources in the form of secondary and primary with data collection techniques, namely through interviews, after the data is systematically compiled and linked from one data to another then will be explained clearly and in detail. The result of the research reveals that the Regulation of the Minister of Law and Human Rights Number 3 of 2018 concerning the terms and procedures for granting parole which is used as a legal basis, but in its implementation there are several obstacles including prisoners who violate disciplinary rules and the public is worried about being exposed to Covid-19from prisoners.